PROBLEMATIKA KEPEMILIKAN SERTIFIKAT PENDIDIK DI INDONESIA - Silm Oktapani (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study examines (a) problems for lecturers who do not have an educator certificate, (b) looking for root causes of difficulties lecturers have educator certificates and (c) looking for solutions for lecturers who do not have an educator certificate. This research is a normative study. The data used is secondary data collected through literature. The results of this study concluded that lecturers must always update data on the Higher Education Data Base. On filling in the self description must be relevant to the questions given and do not copy paste. Lecturers are required to conduct research and publish and do not let the lecturer to falsify scientific work. Use a valid certificate/AA certificate. Persuasive assessments should not be carried out by only one person and also do not allow persuasive assessments with perfect scores to be carried out by the entire committee. Lecturers must know how to take steps in each stage of the certification examination.